2021
DOI: 10.1016/j.jacep.2020.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of the RADPAD Surgical Cap in Reducing Brain Exposure During Pacemaker and Defibrillator Implantation

Abstract: During device implantation the RADPAD ® cap decreased the skin front head exposure but had no impact on brain dose distribution as the exposure comes from upwards scattered radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 14 publications
1
22
0
1
Order By: Relevance
“…Therefore, reduction of scatter radiation at the level of the head is of particular importance. While radiation protection glasses are an effective way to reduce the risk of cataracts, cranial radioprotective surgical caps designed to specifically reducing brain exposure showed no impact on brain dose distribution [14,15] because of upward scatter radiation that enters the skull through the neck. Therefore, there is a clinical need for improved radiation protection for the head.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, reduction of scatter radiation at the level of the head is of particular importance. While radiation protection glasses are an effective way to reduce the risk of cataracts, cranial radioprotective surgical caps designed to specifically reducing brain exposure showed no impact on brain dose distribution [14,15] because of upward scatter radiation that enters the skull through the neck. Therefore, there is a clinical need for improved radiation protection for the head.…”
Section: Discussionmentioning
confidence: 99%
“…Some of them, except one which reports no effect [25], demonstrate its advantage over the ceiling-suspended protective screen, but authors anticipate the effect of lead cap on the head or brain based on the measurements performed on the skin [23][24][25]. The remaining papers, relying on simulations or measurements performed inside phantom head give consistent conclusions and show rather minimal influence of the lead cap on the doses to the head [22,26,27]. The aim of this study is to provide a deeper insight into the influence of the lead free cap on the dose to the skin, the head and the brain of interventional cardiologists by carrying out measurements in both the clinic during real procedures and laboratory in exposure conditions that mimic the real practice.…”
Section: Clinical Measurementsmentioning
confidence: 98%
“…They can differ in terms of shape, weight and lead equivalence. Few papers present the results on protective capabilities of lead or lead free caps but their conclusions, due to different methodologies used, are inconsistent [22][23][24][25][26][27]. Some of them, except one which reports no effect [25], demonstrate its advantage over the ceiling-suspended protective screen, but authors anticipate the effect of lead cap on the head or brain based on the measurements performed on the skin [23][24][25].…”
Section: Clinical Measurementsmentioning
confidence: 99%
“…Operators reported that the comfort level with the cap on during the procedure was 9 on a 1–10-point scale 31 . Interestingly, however, when tested in left subpectoral device implant procedures, with the right half of the operator's front head as the most exposed region, the Radpad cap attenuated the skin fronthead exposure but did not provide protection to the brain 10 . The exposure of the anterior part of the brain is decreased by the skull by 4.5-fold compared with the fronthead skin value; however, this study confirms previous evidence that most of the radiation to a interventionalist's brain originates from scatter radiation from angles not shadowed by a protection cap 26 .…”
Section: Head Protectionmentioning
confidence: 99%
“…Further, brain irradiation can have direct radiation effects on the thyroid and pituitary glands. The use of lead-based cranial dedicated shields may help reduce operator exposure but upward scattered radiation coming from the patient may challenge protection 10 …”
Section: Introductionmentioning
confidence: 99%